Investors' Sentiment in The Nigerian Stock Market: Does Covid-19 Matter? - Babarinde, Gbenga Festus; Adegoke Adewusi, Olusegun; Idera Abdulmajeed , Tajudeen; Hassan Haziel, Yusuf (The International Journal of Accounting and Business Society, 2022)
Purpose: Past studies have focused on psychological and macroeconomic factors as determinants of investor sentiment. However, the 2019 novel coronavirus disease (COVID-19) outbreak has raised the need to determine whether the pandemic shapes investors' sentiment. Hence, this research aims to examine the role of COVID-19 in shaping investors' sentiment in the Nigerian capital market. Methodology: In determining whether COVID-19 matters or not in shaping investor sentiment in the Nigerian capital market, this study applied the Vector Error Correction Model (VECM) and Pearson correlation techniques to the analysis of the weekly time series data on COVID-19 confirmed (positive), discharged and fatal cases and their relationships as well as impacts on the stock (capital) market investors' sentiment in Nigeria for the period 2nd March 2020 to 25th October 2020. Findings: This study confirms a weak positive relationship between COVID-19 and investors' sentiment in the Nigerian stock market. Furthermore, there is evidence that the discharged and fatal cases of COVID-19 have had significant positive impacts on investors' sentiment in Nigeria in the long run, unlike the positive cases, which have had significant negative impacts. In the short-run, however, COVID-19 positive cases have positive while discharged and fatal cases have negative non-significant effects on stock market investors' sentiment in Nigeria. Practical Implications: It is therefore concluded that COVID-19 cases are significant determinants of investors' sentiment in the Nigerian stock market, such that the effects of the pandemic are significant in shaping stock market investors' sentiment in the country. It is high time the regulatory authorities and investment community, particularly investors, considered the long-run implications of the current COVID-19 pandemic on their behaviour and decisions. Originality/Value: This is one of the very few studies in Nigeria that discount the influence of health pandemics such as COVID-19 on the behaviour of investors in the stock market concerning sentiments. Keywords: Investors Sentiment, COVID-19, Nigerian Stock Exchange, Investment Decision. Paper type- Research paper